Phase Diversity-Based Fourier Ptychography for Varying Aberration Correction - Xiang, Meng; Pan, An; Liu, Jinpeng; Xi, Teli; Guo, Xin; Liu, Fei; Shao, Xiaopeng (Frontiers in Physics, 2022)
Fourier ptychography (FP) is geared toward high-resolution imaging with a large field of view efficiently. In the original illumination-based FP scheme, the aberrations in optical systems can be well reconstructed, which plays a prominent role in simple and compact optical arrangements. Unfortunately, the reconstruction strategy for recovering an optical system’s pupil function fails to carefully consider the nature of the field-dependent pupil function in the aperture-scanning FP scheme, which affects the quality of the reconstructed image to a certain extent. Based on this observation, we report a phase diversity-based FP (PDFP) scheme for varying aberration correction. We image USAF resolution target with the proposed PDFP scheme and demonstrate our ability to correct varying aberration and improve image quality. The reported approach allows aperture-scanning FP technology to use simpler optical systems for imaging and may facilitate the further development of FP in practical applications such as industrial inspection and long-distance imaging.